Digital Transformation of Education in Indonesia: A Conceptual Framework For Evaluation - Riko Pandu Wijaya; Komarudin; Aip Badrujaman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
Advances in information and communication technology have driven significant changes in Indonesia's education ecosystem. Various school digitalization initiatives, including the provision of digital devices, learning platforms, and the development of educational information systems, have been launched to support the direction of digital transformation of education. However, these programs are not accompanied by an evaluation framework capable of comprehensively assessing their contribution to the educational transformation process. This research aims to develop a conceptual framework for the evaluation of educational digital transformation that is comprehensive, systematic, and contextual through a study of the implementation of the school digitalization program in Indonesia. The research approach uses the Systematic Literature Review (SLR) method, following the PRISMA framework and the PICO (Population, Intervention, Control, and Outcome) formulation structure. The literature was collected from reputable databases, including Scopus, Google Scholar, and SINTA, which yielded 212 initial articles. After selection, 33 relevant articles remained. The results of the synthesis show that five main dimensions contribute to the evaluation of digital transformation of education, namely: (1) digital infrastructure, (2) learning content and platforms, (3) digital competence, (4) institutional support, and (5) the effectiveness of digital learning. Based on these findings, an evaluation conceptual framework was prepared to support policy formulation and planning for the development of digital schools in a more targeted and sustainable manner.